Sensory experiments psychophysics, race, and the aesthetics of feeling - Fretwell, Erica 1982- (Duke University Press, 2020)
Sight : unreconstructed body images -- Sound : the acoustics of social harmony -- Smell : perfume, women, and other volatile spirits -- Taste : sweet measures and lawless pleasures -- Touch : life writing between skin and flesh -- Coda. Afterlives and antelives of feeling